Estabelecimento de escrita sob controle de ditado como base para a recombinação na leitura e na escrita - Reis, Thaíze de Souza (2013)
Several studies are interested in the acquisition of reading and spelling as well as in the role the acquisition of one ability plays in the acquisition of the other. However, many of these studies focus on reading rather than on spelling. This study aimed to teach spelling skills and verify whether it would affect the reading repertoire. To teach spelling, a constructed response matching to sample task was employed. In this task, a sample (that could be a printed word, a picture, a picture and its correspondent printed word or a dictated word) was presented as well as a pool of randomly chosen letters. Children had to select in the correct order the letters to spell the word correspondent to the sample. Thirty Portuguese words were taught. Five studies were conducted. In Study 1, each word was taught till criterion and once it was achieved the word was no longer presented during training. Two students took part but only one achieved the criterion for the totality of the words. Although the criterion was achieved rapidly for most words, the performance decreased on the posttest probes. Study 2 employed a mixed training: groups of three words were taught together so that in each trial one of the words worked as a sample. Study 3 employed the mixed training and a cumulative baseline: words previously taught were interspersed with words to be taught. Study 4 introduced a new variable, besides the mixed training and the cumulative baseline: a compound sample. In this study, words should be constructed under the control of a sample compounded by a picture and its correspondent printed word. After training, all participants of the Studies 2, 3 and 4 showed high spelling performances and excepting one participant, all of them had great improvements in reading. Reading scores were more variable than spelling scores. Performances with new words (compounded by the syllables of the taught words) were variable and some participants did not show recombinative repertoire. Also, some participants showed performances with some words before they were actually trained. Because of that, Study 5 employed a group design to evaluate the effect of the teaching procedure. The Experimental Group took the teaching procedure lessons (the same version employed in Study 4) while the Control Group was exposed only to the assessment sessions. The Experimental Group performances in spelling, reading and other relations evaluated were significantly higher than the Control Group performances. These results showed that the procedure have been effective in teaching spelling and also in promoting the emerge of reading.